Role of heparan sulfate in sexually transmitted infections - Tiwari, Vaibhav (Oxford University Press, 2012)
Cell surface heparan sulfate (HS), a polysaccharide composed of alternating uronic acid and glucosamine residues, represents a common link that many sexually transmitted infections (STIs) require for infection. Variable modifications within the monomeric units of HS chains together with their unique structural conformations generate heterogeneity, which expands the ability of HS to bind a diverse array of host and microbial proteins. Recent advances made in the field of glycobiology have critically enhanced our understanding of HS and its interactions with microbes and their significance in important human diseases. The role of HS has been elaborated for several STIs to include those caused by herpes simplex virus, human immunodeficiency virus, human papillomavirus, and Chlamydia. In addition, gonorrhea, syphilis, and yeast infections are also dependent on the presence of HS on human target cells. Critical steps such as pathogen adhesion or binding to host cells followed by internalization to enhance intracellular survival and possible spread to other cells are mediated by HS. In addition, HS guided cell signaling plays a role in the development of angiogenesis and inflammation associated with many STIs. Past and ongoing investigations are providing new push for the development of HS-mimetics and analogs as novel prevention strategies against many different STIs. This review article summarizes the significance of HS in STIs and describes how emerging new products that target HS can be used to control the spread of STIs.